High-grade non-muscle invasive urothelial carcinoma in dogs and humans share specific expression of integrin α5β1 - Lucianò, Roberta; Colecchia, Maurizio; Sanvito, Francesca; Locatelli, Irene; Venegoni, Chiara; Di Coste, Alessia; Zani, Davide Danilo; Stranieri, Angelica; Giudice, Chiara; Rigillo, Antonella; Gambini, Matteo; Montorsi, Francesco; et al. (Frontiers in Oncology, 2025)
ObjectiveUrothelial carcinoma (UC) accounts for more than 90% of all bladder cancers both in humans and dogs. Human and canine UC share many genetic mutations and tumor markers and clinical and therapeutic interventions. The unmet clinical needs are similar such as the early detection and treatment of the high-grade residual disease responsible for tumor recurrence and progression. The aim of this study was to investigate the expression of the α5β1 integrin and its specificity in high-grade UC in humans and dogs, a marker recently reported in the human bladder in situ carcinoma and murine model of orthotopic bladder cancer.MethodsExpression of integrin α5β1 was established by immunohistochemistry in 67 human bladder samples [four non-tumor tissues, 10 low-grade, 10 intermediate-grade, and 43 high-grade non-muscle invasive bladder cancer (NMIBC)] and 12 canine bladder tumor specimens.ResultsThe α5β1 integrin was not expressed by urothelial cells in the conditions of inflammatory cystitis, actinic cystitis, benign hyperplasia, and low/intermediate grade NMIBC; it was identified as a specific marker expressed only by the malignant cells in the urothelium in 81% of human and all canine high-grade NMIBC.ConclusionsThe expression of α5β1 integrin is a specific marker of high-grade UC located in the urothelium of humans and dogs and might be tested for targeted delivery of contrast agents or drugs. Given the close similarity between high-grade UC in humans and dogs, basic research in the two species and comparative data analysis could strengthen the prospects for rapid development of an improved clinical strategy for the identification and treatment of the small neoplastic lesions responsible for residual high-grade in both species.